The murder epidemic: A global comparative study - Simplice Asongu; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2017)
We build on literature from policy and academic circles to assess if Latin America is leading when it comes to persistence in homicides. The focus is on a global sample of 163 countries for the period 2010 to 2015. The empirical evidence is based on Generalised Method of Moments. The following main finding is established. The region with the highest evidence of persistence in homicides is sub-Saharan Africa (SSA), followed by Latin America, the Middle East and North Africa (MENA) and then by Europe & Central Asia (ECA). In order to increase room for policy implications, the dataset is decomposed into income levels, religious domination, landlockedness and legal origins. From the conditioning information set, the following factors account for persistence in global homicides: crime, political instability and weapons import positively affect homicides whereas the number of "security and police officers" has the opposite effect.
Keywords: K42; P50; 330; Homicides; Global evidence; Persistence; Latin America